Eastern traditions in fables of storytellers of the land of Syr (Turmagambet, Zhusip, Omar) - Zhanbershiyeva Ұ.; Oralova Г.С.; Tulebayeva А.Т.; Kamisheva Г.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article deals with the issue of reflecting oriental traditions in the fables of such storytellers of the land of Syr as Turmagambet Iztleuov, Shorayaktyn Omary, Kete Zhusip, Kanly Zhusip Kadirbergenuly, Bazar Zhyrau and others. A scientific analysis of these traditions in the works of poets-storytellers Syr is given: similar plots are revealed, repetition of motives, continuity; the cognitive function of the expressive means of speech used in fables to attract the attention of readers is analyzed. On the example of fables created on the basis of oriental plots, conclusions are drawn about the ways of thinking of storytellers, arguments are given. The article reveals the meaning of Eastern traditions in the work of storytellers of the land of Syr. An assessment is made of the educational significance of the fables of Turmagambet, Zhusip and Omar. Using the example of the fables-verses of these three poets, it is possible to identify the artistic features of the literary heritage of the storytellers of the land of Syr. Analyzing the oriental nature of the fables and poems, we come to the conclusion that the work of the poets and storytellers of Syr is an integral part of the national literature. Based on the fundamental research of Kazakh scientists, an attempt is made to comprehensively reveal oriental motives; world and national cultural and literary connections and the significance of the Eastern tradition are revealed. The contribution of Syr’s storytellers to the development of this method is considered, a scientific description of their poetic worldview is given. From a cognitive point of view, the oriental model and instructive thoughts reflected in fables are analyzed. The article reveals the features of the Eastern tradition in the fables of the poets-narrators of the land of Syr, and proves their national value.